Short and long term retention in antiretroviral care in health facilities in rural Malawi and Zimbabwe - Rasschaert Freya; Koole Olivier; Zachariah Rony; Lynen Lut; Manzi Marcel; Van Damme Wim (BMC, 2012)
Abstract Background Despite the successful scale-up of ART services over the past years, long term retention in ART care remains a major challenge, especially in high HIV prevalence and resource-limited settings. This study analysed the short (<12 months) and long (>12 months) term retention on ART in two ART programmes in Malawi (Thyolo district) and Zimbabwe (Buhera district). Methods Retention rates at six-month intervals are reported separately among (1) patients since ART initiation and (2) patients who had been on ART for at least 12 months, according to the site of ART initiation and follow-up, using the Kaplan Meier method. 'Retention' was defined as being alive on ART or transferred out, while 'attrition' was defined as dead, lost to follow-up or stopped ART. Results In Thyolo and Buhera, a total of 12,004 and 9,721 patients respectively were included in the analysis. The overall retention among the patients since ART initiation was 84%, 80% and 77% in Thyolo and 88%, 84% and 82% in Buhera at 6, 12 and 18 months, respectively. In both programmes the largest drop in ART retention was found during the initial 12 months on ART, mainly related to a high mortality rate in the health centres in Thyolo and a high loss to follow-up rate in the hospital in Buhera. Among the patients who had been on ART for at least 12 months, the retention rates leveled out, with 97%, 95% and 94% in both Thyolo and Buhera, at 18, 24 and 30 months respectively. Loss to follow-up was identified as the main contributor to attrition after 12 months on treatment in both programmes. Conclusions To better understand the reasons of attrition and adapt the ART delivery care models accordingly, it is advisable to analyse short and long term retention separately, in order to adapt intervention strategies accordingly. During the initial months on ART more medical follow-up, especially for symptomatic patients, is required to reduce mortality. Once stable on ART, however, the ART care delivery should focus on regular drug refill and adherence support to reduce loss to follow up. Hence, innovative life-long retention strategies, including use of new communication technologies, community based interventions and drug refill outside the health facilities are required.